Effects of hypoxia-inducible factor-prolyl hydroxylase inhibitors vs. erythropoiesis-stimulating agents on iron metabolism in non-dialysis-dependent anemic patients with CKD: A network meta-analysis - Yang, Junlan; Xing, Jie; Zhu, Xiaodong; Xie, Xiaotong; Wang, Lina; Zhang, Xiaoliang (Frontiers in Endocrinology, 2023)
Objective To compare the effects of five hypoxia-inducible factor-prolyl hydroxylase domain inhibitors (HIF-PHIs), two erythropoiesis-stimulating agents (ESAs), and placebo on iron metabolism in renal anemia patients with non-dialysis-dependent chronic kidney disease (NDD-CKD). Method Five electronic databases were searched for studies. Randomized controlled clinical trials comparing HIF-PHIs, ESAs, and placebo in NDD-CKD patients were selected. The statistical program used for network meta-analysis was Stata/SE 15.1. The main outcomes were the change in hepcidin and hemoglobin (Hb) levels. The merits of intervention measures were predicted by the surface under the cumulative ranking curve method. Results Of 1,589 original titles screened, data were extracted from 15 trials (3,228 participants). All HIF-PHIs and ESAs showed greater Hb level–raising ability than placebo. Among them, desidustat demonstrated the highest probability of increasing Hb (95.6%). Hepcidin [mean deviation (MD) = -43.42, 95%CI: -47.08 to -39.76], ferritin (MD= -48.56, 95%CI: -55.21 to -41.96), and transferrin saturation (MD = -4.73, 95%CI: -5.52 to -3.94) were decreased, while transferrin (MD = 0.09, 95%CI: 0.01 to 0.18) and total iron-binding capacity (MD = 6.34, 95%CI: 5.71 to 6.96) was increased in HIF-PHIs versus those in ESAs. In addition, this study observed heterogeneity in the ability of HIF-PHIs to decrease hepcidin. Compared with darbepoetin, only daprodustat (MD = –49.09, 95% CI: –98.13 to –0.05) could significantly reduce hepcidin levels. Meanwhile, daprodustat also showed the highest hepcidin-lowering efficacy (84.0%), while placebo was the lowest (8.2%). Conclusion For NDD-CKD patients, HIF-PHIs could ameliorate functional iron deficiency by promoting iron transport and utilization, which may be achieved by decreasing hepcidin levels. Interestingly, HIF-PHIs had heterogeneous effects on iron metabolism. Systematic review registration https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=242777, Identifier CRD42021242777.